Welding skills - Moniz B. J (American technical publishers, 2004)
Welding skills,3rd Ediction,is the product of an extensive revision effort to address of the welding trade and the latest welding technology .Now in full color ,this comprehensive test has been completely updated and expanded to continua the tradition of an industry -leading instructional tool .anew contemporary desin detailed illustrations,descriptive photographs and concise test enhance the learning process step-by-step,current AWS terminology ,key points,and informative factoids supplement essential content throuhout the test